2005
DOI: 10.1002/tox.20123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proteases in guts ofDaphnia magnaand their inhibition byMicrocystis aeruginosaPCC 7806

Abstract: Many cyanobacteria produce peptides that inhibit mammalian proteases. The hypothesis that inhibitors of mammalian proteases produced by cyanobacteria also interfere with digestive proteases of natural cladoceran grazers was tested by comparing the effects of cyanobacterial protease inhibitors on digestive proteases from Daphnia magna and on commercially available bovine proteases. The major digestive proteases of D. magna are trypsins and chymotrypsins, which differ from those of bovine origin in substrate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 50 publications
4
71
0
2
Order By: Relevance
“…This suggests that cyanobacterial trypsin and chymotrypsin inhibitors constitute an antiherbivore defence that interferes with major digestive proteases in D. magna. In D. magna grown on the green alga S. obliquus, nine different proteases have been distinguished using zymograms (Von Elert et al, 2004), and five proteases ranging from 22 to 75kDa were identified as trypsins through the use of synthetic inhibitors (Agrawal et al, 2005). Here, effects of the synthetic inhibitor chymostatin and the cyanobacterial chymotrypsin inhibitors cyanopeptolin 954 and nostopeptin BN920 reveal that the remaining three proteases in D. magna with a molecular mass ranging from 16 to 24kDa are chymotrypsins.…”
Section: Effects Of Cyanobacterial Protease Inhibitors On D Magnamentioning
confidence: 93%
See 1 more Smart Citation
“…This suggests that cyanobacterial trypsin and chymotrypsin inhibitors constitute an antiherbivore defence that interferes with major digestive proteases in D. magna. In D. magna grown on the green alga S. obliquus, nine different proteases have been distinguished using zymograms (Von Elert et al, 2004), and five proteases ranging from 22 to 75kDa were identified as trypsins through the use of synthetic inhibitors (Agrawal et al, 2005). Here, effects of the synthetic inhibitor chymostatin and the cyanobacterial chymotrypsin inhibitors cyanopeptolin 954 and nostopeptin BN920 reveal that the remaining three proteases in D. magna with a molecular mass ranging from 16 to 24kDa are chymotrypsins.…”
Section: Effects Of Cyanobacterial Protease Inhibitors On D Magnamentioning
confidence: 93%
“…have been shown to inhibit trypsin activity in crude extracts of the cladocerans Moina macrocopa (Agrawal et al, 2001), D. magna (Rohrlack et al, 2003;Agrawal et al, 2005) and Daphnia sp. (Blom et al, 2006).…”
Section: Effects Of Cyanobacterial Protease Inhibitors On D Magnamentioning
confidence: 99%
“…These protease inhibitors have shown to cause inhibition of digestive proteases belonging to a variety of classes and hence can be related to subacute toxicity (Rohrlack et al 2003, Agrawal et al 2005a, b, Agrawal 2010). The present study shows that while grown under similar conditions and nutrients in vitro for many generations, the three isolates of Oscillatoria differed in their protease-inhibiting capabilities despite of similar protease inhibitory potential at the time of harvest from their natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…All the three extracts were pooled, dried under vacuum and redissolved in 1 ml of 50 % methanol. This extract was used as a source of protease inhibitors from cyanobacteria (Agrawal et al 2005a). …”
Section: Preparation Of Cyanobacterial Extractsmentioning
confidence: 99%
See 1 more Smart Citation